Likelihood of Mental Health and Substance Use Treatment Receipt among Pregnant Women in the USA. - Salameh, Taghreed N.; Hall, Lynne A.; Crawford, Timothy N.; Staten, Ruth R.; Hall, Martin T. (International Journal of Mental Health & Addiction, 2021)
To explore predictors of mental health and substance use treatment receipt in pregnant women in the USA. Secondary analysis of data from the 2008–2014 National Survey on Drug Use and Health was conducted. Two logistic regression models were run to identify predictors of mental health treatment receipt among pregnant women aged 18–44 years with mental health problems (N = 1106) and predictors of substance use treatment among pregnant women with substance use disorders (N = 521). Forty four percent of pregnant women with mental health problems received mental health treatment, and only 13% of pregnant women with substance use disorders received substance use treatment. Women with anxiety disorder (vs. no disorder) (adjusted odds ratio (AOR): 17.3, 95% Confidence Interval (CI): 8.6–34.8), major depression (vs. no depression) (AOR: 2.48, 95% CI: 1.44–4.27), higher level of serious psychological distress (AOR: 1.06, 95% CI: 1.003–1.12), college (vs. less than high school) education (AOR: 2.84, 95 %CI: 1.36–5.91), and health insurance coverage (vs. no coverage) (AOR: 2.34, 95% CI: 1.16–4.71) had higher odds of mental health treatment receipt. African American (AOR:.38, 95% CI:.20–.74) and Hispanic women (AOR:.17, 95% CI:.05–.59) had lower odds for mental health treatment relative to Whites. The best set of predictors of substance use treatment receipt included NonWhite (vs. White ethnicity) (AOR:.39, 95% CI:.19–.80), large (vs. small urban) residency (AOR: 4.38, 95% CI: 1.84–10.45), alcohol and illicit drug use disorders (vs. no disorder) (AOR: 2.92, 95% CI: 1.48–5.78; AOR: 8.70, 95% CI: 3.32–22.76; respectively), and comorbid anxiety/depression disorder (vs. no disorder) (AOR: 3.13, 95% CI: 1.40–7.02). The common barriers reported by pregnant women who perceived unmet need for mental health treatment included perceived cost, opposition to treatment, and stigma, regardless of their disorder. The majority of pregnant with mental health/substance use disorders do not receive treatment. More policy and treatment initiatives that address barriers to and predictors of treatment receipt are needed to help this vulnerable population of pregnant women to gain access to mental health and substance use treatment.